Breast cancer as a significant social problem - Husejko, Jakub; Porada, Mateusz; Bieniek, Daria; Skierkowska, Natalia; Prylińska, Monika; Ruszkowska, Nastazja; Nawrocka, Agnieszka; Sępka, Justyna; Szczesna, Natalia; Swierczek, Pamela; Pałka, Julianna; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2019)
Background: This article is devoted to the topic of breast cancer, which is a very important and overlooked problem by many women. This cancer is the most common malignancy in women in developed countries. It also creates an increasing problem in developing countries and causes high mortality. Early diagnoses of neoplastic lesions and rapid implementation of therapy in most cases allow for successful treatment its prognosis . Self-control is very important, women should examine their breasts by palpation. Further research to diagnose breast cancer are: mammography (MMG), ultrasonography (USG), magnetic resonance (MR), positron emission tomography (PET) and microscopic examination.Material and Methods: In this article, it was analyzed by the latest literature on risk factors, epidemiology, diagnosis and treatment of breast cancer. Articles were searched from PubMed and Google Scholar.Results: Breast cancer risk factors have been shown to be early menstruation, high women's height, high body mass (especially fat content) and hyperinsulinaemia. In addition, genetic factors play an important role. Research also confirms that highly-used cleaners, and at their head, DDP (dichlorodiphenyltrichloroethane) affect the formation of breast cancer. This is the third most common cause of death in women aged 60-85. In treatment, an individual approach to each patient is important. Older women individually discuss the methods of treatment with the doctor, because it gives beneficial results of therapy.Conclusions: Breast cancer has become a very important medical and social problem in older women. Mass media are needed to disseminate knowledge, topics related to treatment and to support the sick. In older women, treatment is more aggressive, and in addition to radiotherapy, a partial mastectomy is performed. Breast cancer is a tought term for woman’s in all age. It is related with fear and loss of self—confidence.